Research hotspots and frontiers in the tumor microenvironment of colorectal cancer: a bibliometric study from 2014 to 2024 - He, Xinran; Xie, Tingyi; Shi, Li; Kuang, Xuyi; Li, Lei; Shang, Xingyu; Fu, Bo (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) is the second leading cause of cancer deaths globally, which poses a heavy burden on our healthcare and economy. In recent years, increasing researches suggest that the tumor microenvironment (TME) influences cancer onset, progression, metastasis, and treatment. This has become a popular direction for researching and attacking cancer. However, to date, there is no bibliometric analysis of colorectal cancer and tumor microenvironment from 2014 to 2024. This study aims to provide a comprehensive picture of the current research status, hotspots, and future trends in this field from a bibliometric perspective.MethodsIn this study, the publications about colorectal cancer and tumor microenvironment from 2014 to 2024 were searched based on the Web of Science Core Collection database. Then we analyzed and visualized the data using CiteSpace, VOSviewer, bibliometrix package, and Microsoft Excel 2019.ResultsA total of 748 publications were included in our study, and the number of publications entered a period of rapid growth after 2019. China and the United States are the major research and collaboration centers in this field. Elkord, Eyad is the most prolific author, and Frontiers in Immunology is the journal that published the most papers on the TME of CRC. In addition, keyword and cluster analysis showed that immune checkpoint inhibitors, cancer-associated fibroblasts, macrophage polarization, intestinal microbiota, colorectal cancer liver metastasis, drug resistance, scRNA-seq, etc. may be the research hotspots and trends in this field.ConclusionsColorectal cancer and tumor microenvironment research is in the developmental stage, and strengthening international cooperation can help to drive this field forward. The main components and signaling in TME, CRC immunotherapy, colorectal cancer liver metastasis, and new research techniques are the hot research directions in this domain. Our findings will provide scholars with an up-to-date perspective on the current state of research, hotspots, and future trends in this field.